Art 21 art in the twenty-first century 2 - Sollins, Susan; Sollins, Marybeth (New York, N.Y. Abrams, 2003)
Companion volume to the second season of the PBS television series of the same title, introducing 16 contemporary American artists and their work.
Eleanor Antin -- Janine Antoni -- Charles Atlas -- Vija Celmins -- Walton Ford -- Trenton Doyle Hancock -- Tim Hawkinson -- Elizabeth Murray -- Gabriel Orozco -- Raymond Pettibon -- Paul Pfeiffer -- Martin Puryear -- Collier Schorr-- Kiki Smith -- Do-Ho Suh -- Kara Walker.
Keywords: Art, American -- 21st century; Art, American -- 20th century; Artists -- United States -- Interviews; Artists -- United States -- Biography